Vorasidenib- A Paradigm Shift in IDH1- or IDH2-Mutant Low-Grade Glioma Treatment - Malik, Hurais; Hudaib, Muhammad; Rehman, Abdul (Journal of the Pakistan Medical Association, 2024)
Low-grade gliomas (LGGs) pose significant challenges in cancer research and treatment due to their infiltrative nature and tendency for recurrence, making them the most common brain tumour in adults. Most of the LGGs have the propensity to cause notable alterations in the microenvironment of the tumour thus making them difficult to treat. These alterations can be attributed to the prevalent mutations in the genes that produce isocitrate dehydrogenase (IDH) enzymes, especially in grade 2 diffuse gliomas. [1] Despite its inability to provide a complete cure, chemoradiation has been adopted as the standard therapy in grade 3 gliomas since it can lead to long-lasting remission. Chemoradiotherapy, when administered promptly, can help prevent tumour progression, and recurrence after surgery and improve long-term outcomes. Nevertheless, immediate adjuvant chemoradiotherapy is not administered in patients afflicted with tumours containing IDH mutant grade 2 gliomas. This decision is often made to circumvent potential harm such as radiation-induced cognitive problems, chemotherapy-related DNA mutations, and other negative effects on their health. [2] Due to the intricacies associated with the treatment decisions and the inclination to delay aggressive therapies to avoid adverse events, creates a necessity for a novel therapeutic strategy that is both effective and well tolerated. Vorasidenib, an oral medication specifically designed to deal with IDH mutations has displayed promise despite existing challenges. By aiming to specifically target aberrant metabolic pathways triggered by mutant IDH enzymes, Vorasidenib offers a potential treatment capable of interrupting tumour growth and could subsequently result in better patient outcomes. Among the many reasons that make Vorasadenib an appealing option are its capability to penetrate the blood-brain barrier and its promising safety profile, resulting in effective treatment while alleviating potential side effects. [3] Vorasidenib’s efficacy is derived from its ability to halt the metabolic cascades driven by mutant IDH enzymes thus leading to decreased progression of the gliomas. Clinical studies elicit the substantial value Vorasadenib has to offer by enhancing progression-free survival and postponing the advancement of the illness in patients with grade 2 IDH-mutant gliomas. This offers an optimistic prospect for delaying the need for more aggressive treatments in these patients. [2,4] Hence, to conclude Vorasadenib can transform treatment norms and enhance outcomes for those suffering from IDH-mutant LGG. Furthermore, it is crucial to investigate different treatment combinations, finding markers that would help assess clinical response to treatment, which in turn would be an important milestone in the treatment journey.